An optimized method of partial discharge data retrieval technique for phase resolved pattern - Eka Putra Waldi; Aulia Aulia; Ariadi Hazmi; Hairul Abral; Syukri Arief; Mohd Hafizi Ahmad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The measurement of phase resolved partial discharge requires a gigantic memory capacity to store all the waves of the PD test results. This limitation eventually hinders the testing. It is necessary to optimize on the aspect of memory storage capability to reduce the storage requirements. In light of foregoing, the partial discharge data retrieval techniques with sampling rate methods were used to detect the peak of partial discharge as well as the PD constituent representatives. The optimization process was performed by using integration of oscilloscope and LabVIEW software. The partial discharge data recording can be easily confined to the points of the partial discharge occurrence only. As results, the storage points were reduced by taking wave magnitude associated with PD, thereby resulting in more representative data. Therefore, this optimized method was able to reduce the file size of the test results up to 97 percent of PD original size thereby decreasing the usage of hard disk storage.